LncRNA LOC285758 Induced Non-Small Cell Lung Cancer Development through Up-Regulating CDK6 by Sponge Adsorption of miRNA-204 - Xiangtao Yu; Dianjun Liu; Lin Wang; Liguo Wang (Tehran University of Medical Sciences, 2022)
Background: Non-coding RNA played one pivotal role in NSCLC in terms of pathogenesis and progression. We aimed to determine the LncRNA, which can be one new potential target for NSCLC treatment and its possible mechanisms from Jan 2017 to Aug 2020. Methods: Gene LOC285758, which produced new cells in tumor cellular system, was knocked out. Its specific effects were tested in terms of cellular phenotype. LOC285758 was chosen to target for miRNA as well as downstream mRNA targeted by miRNA, which verified the combination predicted before. Specific impacts brought from miRNA on NSCLC cells were examined. At last, dynamic impacts produced through miRNA and LOC285758 on mRNA expression and NSCLC cellular phenotype were examined. Results: LOC285758 expression was up-regulated in tissues and cells from NSCLC. Knocking out gene LOC285758 could repress cellular survival and migration of A549 and H292 cells. miRNA-204 was repressed via LOC285758 targeting. miRNA-204 over-expressing repressed invasion ability of NSCLC cells and CDK6 targeted by miRNA-204. CDK6 knocking out suppressed survival and migration of NSCLC cells. The influence brought from gene LOC285758 knocking out could be reversed through suppressing miRNA-204, causing up-regulated CDK6 as well as LOC285758 expression in NSCLC tissues. miRNA-204 was negatively correlated with CDK6 as well as LOC285758, respectively. Nonetheless, CDK6 possessed the positive relationship with LOC285758. Conclusion: An axis of lncRNA LOC285758/miRNA-204/CDK6 can modulate NSCLC cells in terms of migration as well as survival.